A Summer of Birds : John James Audubon at Oakley House - Heitman, Danny, 1964- (Book collections on Project MUSE., 2008)
Over the summer of 1821, a cash-strapped John James Audubon worked as a tutor at Oakley Plantation in Louisiana's rural West Feliciana Parish. This move initiated a profound change in direction for the struggling artist. Oakley's woods teemed with life, galvanizing Audubon to undertake one of the most extraordinary endeavors in the annals of art: a comprehensive pictorial record of America's birds. That summer, Audubon began what would eventually become his four-volume opus, Birds of America. In A Summer of Birds, Danny Heitman recounts the season that shaped Audubon's destiny, sorting facts from romance to give an intimate view of the world's most famous bird artist. A new preface marks the two-'hundredth anniversary of that eventful interlude, reflecting on Audubon's enduring legacy among artists, aesthetes, and nature lovers in Louisiana and around the world.